Collaboration and Reflective Practices in Field-Based Learning: Strengthening Academic Literacy through Digital Documentation - Yazid Fanani; Laela Rosidha; Fety Fitriana Hertika; Ardhana Januar Mahardhani (Salus Publica: Journal of Community Service, 2025)
This research seeks to examine how teamwork, reflective methods, and digital records in field-based learning enhance academic literacy in postgraduate students. The program was carried out via a field study in Semarang, engaging key partner organizations such as Universitas PGRI Semarang (UPGRIS), Semesta School, the Kota Tua heritage area, and the Grand Mosque of Central Java (MAJT). Using a descriptive qualitative method, data were collected via participatory observation, interviews, digital records, and reflective group discussions. The results indicate that collaboration among institutions offers valuable empirical environments that allow students to link theoretical ideas with practical applications, especially in fields like educational governance, digital innovation, cultural preservation, and spiritual leadership. Reflective practices act as vital tools that enable students to interpret field experiences, participate in analytical processing, and convert observations into a more profound academic comprehension. Simultaneously, digital records improve observational precision, deepen reflective involvement, and bolster academic claims with visual and multimodal proof. The research finds that combining collaboration, reflection, and digital documentation creates a comprehensive learning structure that effectively enhances students’ academic writing abilities, critical thinking, and overall academic literacy in the context of Education 5.0. The research suggests the necessity for more organized, technology-enhanced field learning frameworks to maximize academic and professional learning results for graduate students.